Public Health Aspects in Planning and Development of Kotabaru, Yogyakarta: Aspek Kesehatan Masyarakat dalam Perencanaan dan Pembangunan Kotabaru, Yogyakarta - Sari, Vivi Sandra (BRIN, 2023)
This article discusses the reconstruction of the public health aspect of urban planning based on archaeological remains and historical records. The research location is Kotabaru, Yogyakarta, a European settlement in the early 20th century. A desk research was conducted using archives, journal articles, and theses related to the aspect. A survey was also conduct to record archaeological remains in Kotabaru. Then, analysis was conducted with observations on variables of clean-water supply, waste disposal facilities, healthcare facilities, and open space. The results revealed that Kotabaru, designed following the Garden City concept, gave attention to health aspects. Kotabaru is completed with clean-water pipes, waste disposal in the form of sewers/riool and assanering, healthcare facilities Zendingsziekenhuis Petronella and Militier Hospitaal, and open space Sport Terrein. The result shows that city planners have considered public health aspects to create a clean and healthy city environment.